How Marketing Communication Affect Consumer Purchase Intention in Social Media Context (Case Study: MSMEs Business in Indonesia) - Heni Iswati; Muhammad Iqbal Al 'Mudatsir; Nora Andira Brabo; Rinny Meidiyustiani (International Journal of Social Service and Research (IJSSR), 2023)
The rapid development of the internet has driven changes in marketing communication strategies, from communication through traditional mass media to using communication on the internet that utilizes social media. Marketing communication through social media can help micro, small and medium-sized businesses introduce their brands and products to consumers at a lower cost than through traditional media. The study aims to find out the influence of social media communication forms on brand equity, brand attitudes and consumer purchase intentions built from Consumer Decision Model. This study focus on selected UMKM (Micro, small and medium enterprises-MSMEs) brands in area of food and beverages which business are relatively new to the market and have lower than 5000 followers in social media Instagram. Total number of 102 respondents are selected for online survey by convenience sampling method and a structural equation model (PLS-SEM) with Smart PLS software use as an analysis tool for limited data. The results of this study showed that firm created communication had a positive and significant effect on brand equity but had no significant effect on brand attitudes. User generated communication has a positive and significant effect on brand equity and brand attitudes. Brand attitudes have a positive and significant effect on brand equity. Brand attitudes have a positive and significant influence on consumer purchase intention. Brand equity has a positive and significant effect on purchase intention. Implications and limitations are discussed further.